Pengaruh Model Pembelajaran POGIL (Process Oriented Guided Inquiry Learning) Berbantuan LKPD Terhadap Peningkatan Kemampuan Literasi Sains Peserta Didik - Nur Fazri Husna; Syarifah Rita Zahara; Tulus Setiawan; Nuraini Fatmi; Sudirman Sudirman (Lembaga Bale Literasi, 2025)
The background of the problem underlying the research is the low scientific literacy of student. The objectives of the study are: (1) to determine the effect of the POGIL learning model assisted by LKPD on students’ scientific literacy skills (2) to determine whether there is an increase in students’ scientific literacy skills. The study uses a quasi-experimental method of non-equivalent design (pretest and posttest) control group design. The purposive sampling technique took 42 students consisting of 26 students of class XI MIA 1 as the experimental class and 26 students as the control class. The instrument was in the form of a pretest-posttest test in the form of multiple choice questions of 10 items. Data analysis used normality, homogeneity, hypothesis and n-gain tests. The results obtained, the independt sample test on SPSS version 20 obtained a sig (2-tailed) result of 0.000